PELATIHAN USAHA PEMBUATAN ROTI “NGAWI BAKERY” UNTUK MENINGKATKAN UMKM DI KELURAHAN SAGULUNG KOTA KECAMATAN SAGULUNG, KOTA BATAM - Megah, Suswanto Ismadi; Artanto , Tri; Sugiharti , Sri; Maileni , Dwi Afni (ASOSIASI IDEBAHASA KEPRI, 2025)
Abstract Small and medium enterprises managed by Mr. Parno, a 2nd grade elementary school graduate, are something extraordinary, because with a very minimal educational background but are able to provide jobs for many people. In this PKM activity, input is provided on how this UMKM business can grow rapidly. Home-based bread businesses that are managed by bringing the Brand Image from their hometown, namely Ngawi Regency, East Java, are able to compete in big cities like Batam. With the name